Removal of haloacetonitrile by adsorption on thiol-functionalized mesoporous composites based on natural rubber and hexagonal mesoporous silica - Yaowalak Krueyai (2018)
© 2015 Korean Society of Environmental Engineers. Haloacetonitriles (HANs) are nitrogenous disinfection by-products (DBPs) that have been reported to have a higher toxicity than the other groups of DBPs. The adsorption process is mostly used to remove HANs in aqueous solutions. Functionalized composite materials tend to be effective adsorbents due to their hydrophobicity and specific adsorptive mechanism. In this study, the removal of dichloroacetonitrile (DCAN) from tap water by adsorption on thiol-functionalized mesoporous composites made from natural rubber (NR) and hexagonal mesoporous silica (HMS-SH) was investigated. Fourier-transform infrared spectroscopy (FTIR) results revealed that the thiol group of NR/HMS was covered with NR molecules. X-ray diffraction (XRD) analysis indicated an expansion of the hexagonal unit cell. Adsorption kinetic and isotherm models were used to determine the adsorption mechanisms and the experiments revealed that NR/HMS-SH had a higher DCAN adsorption capacity than powered activated carbon (PAC). NR/HMS-SH adsorption reached equilibrium after 12 hours and its adsorption kinetics fit well with a pseudo-second- order model. A linear model was found to fit well with the DCAN adsorption isotherm at a low concentration level.